Las resoluciones de restitución de menores en la Unión Europea: el caso Rinau - Caamiña Domínguez, Celia M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
This study deals with a case of child abduction in the field of Council Regulation (EC) No 2201/2003 concerning jurisdiction and the recognition and enforcement of judgments in matrimonial matters and the matters of parental responsibility, repealing Regulation (EC) No 1347/2000. In Case C 195/08 PPU, one of the main questions lies in answering whether a decision of restitution adopted by a court of the Member State of origin, that has been certified under Article 42 of the Regulation, complies with the procedures of the Regulation, when a court of the Member State where the child is wrongfully retained has also taken a decision of restitution. The key of this case lies in the fact that the court of the Member State where the child is wrongfully retained took the decision of restitution after having taken a non-return decision that had been brought to the attention of the court of the Member State of origin.